POLITICAL STABILITY AND ECONOMIC DEVELOPMENT UNDER THE CHINESE COMMUNIST PARTY - Wang Hao Ran; Zhao Xin Yi; Li Jian Hao; Lin Mei Xin Yu Jing; Chen Yu An Zhi Xuan (CV. Tirta Pustaka Press, 2026)
This study examines the central role of the Chinese Communist Party (CCP) in shaping political stability and national economic development in contemporary China However, limited studies have systematically examined the institutional mechanisms linking political stability and economic development under the CCP. Utilizing a qualitative document-based approach, the study analyzes policy reports, party congress documents, and peer-reviewed literature using thematic content analysis. The findings reveal three key mechanisms: ideological alignment, bureaucratic coordination, and centralized policy integration, but from a coherent institutional framework that aligns policy priorities across multiple administrative layers. This coherence reinforces the CCP’s legitimacy and enables coordinated implementation of national economic strategies. The results also show a symbiotic relationship between stability and development: sustained economic growth strengthens political legitimacy, while political order provides the conditions necessary for developmental continuity. Nevertheless, the study identifies inherent tensions within China’s governance model, particularly those arising from over-centralization, limited administrative flexibility, and growing societal complexity. These challenges indicate that the long-term sustainability of China’s political–economic model depends on the CCP’s ability to balance centralized authority with adaptive governance. This study contributes by proposing an integrated analytical framework linking institutional governance and developmental outcomes in authoritarian systems. The findings provide insights for policymakers and scholars on governance strategies in centralized political systems